Injectable, Magnetic Plum Pudding Hydrogel Composites for Controlled Pulsatile Drug Release - Maitland, Danielle (My University, 2014)
Injectable, in-situ gelling magnetic plum pudding hydrogel composites were fabricated by entrapping superparamagnetic iron oxide nanoparticles (SPIONs) and thermosensitive N-isopropylacrylamide (NIPAM)-co–N-isopropylmethacrylamide (NIPMAM) microgels in a pNIPAM-hydrazide/carbohydrate-aldehyde hydrogel matrix. The resulting composites exhibited significant, repeatable pulsatile release of 4 kDa FITC-dextran upon exposure to an alternating magnetic field. The pulsatile release from the composites could be controlled by altering the volume phase transition temperatures of the microgel particles (with VPTTs over 37°C corresponding to improved pulsatile release) and changing the microgel content of the composite (with higher microgel content corresponding to higher pulsatile release). By changing the ratio of dextran-aldehyde (which deswells at physiological temperature) to CMC-aldehyde (which swells at physiological temperature) in the composites, bulk hydrogel swelling and thus pulsatile release could be controlled; specifically, lower CMC-aldehyde contents resulted in little to no composite swelling, improving pulsatile release. In vitro cytotoxicity testing demonstrated that the composite precursors exhibit little to no cytotoxicity up to a concentration of 2000 µg/mL. Together, these results suggest that this injectable hydrogel-microgel composite hydrogel may be a viable vehicle for in vivo, pulsatile drug delivery.
Keywords: Controlled Release; Pulsatile Release; Hydrogels; Microgels; Super paramagnetic iron oxide nanoparticles; Magnetic; Biomaterials; Other Biomedical Engineering and Bioengineering; Other Chemical Engineering; Polymer Science; Biomaterials